Crystalline electric field splitting in YbNi4P2 measured by inelastic neutron scattering. Issue 3 (16th January 2013) - Huesges, Zita; Stockert, Oliver; Koza, Michael Marek; Krellner, Cornelius; Geibel, Christoph; Steglich, Frank
Abstract The heavy fermion (HF) compound YbNi4P2 is a promising new system for the study of ferromagnetic quantum criticality. Its particular crystal structure in which the Yb ions form chains along the c‐axis might cause quasi‐1D magnetic interactions. In thermodynamic and transport measurements, highly anisotropic behaviour has been observed. To clarify the role of the crystalline electric field (CEF) on this anisotropy, we have measured its level scheme by inelastic neutron scattering. We observed a broad magnetic excitation feature between 7 and 13 meV that is composed of two or three CEF transitions. We discuss the probability of an additional CEF level at either very high or very low energy.